Comparison of the impact of epigallocatechin gallate and ellagic acid in an experimental cataract model induced by sodium selenite - Ergen, Irfan; Turgut, Burak; Ilhan, Nevin (Ijo Press, 2017)
AIM: To compare the potential protective effects of epigallocatechin gallate (EGCG) and ellagic acid (EA) in an experimental cataract model. METHODS: Twenty-eight Spraque-Dawley rat pups were assigned into four groups. All the rats, except for those in the control group, were injected subcutaneously sodium selenite to induce experimental cataract on the postpartum ninth day, and between 10th and 14th days. Rats in the sham, EGCG, and EA groups were intraperitoneally administered 50 mg/(kg.d)saline solution, 50mg/(kg.d) EGCG and 200 mg/(kg.d) EA, respectively. The reduced glutathione (GSH) and malondialdehyde (MDA) levels, total antioxidant status (TAS) and total oxidant status (TOS) in lens supernatants were measured. RESULTS: The mean cataract gradings in EGCG and EA groups were found to be significantly lower than that in sham group (P<0.001). The mean GSH levels and TASs in EGCG and EA groups were significantly higher than that in sham group while mean MDA levels and TOSs in EGCG and EA groups were significantly lower than that in the sham group (P<0.001). CONCLUSION: EGCG and EA have protective effects on cataract development via the inhibition of oxidative stress.
Keywords: sodium selenite; experimental cataract; epigallocatechin gallate; ellagic acid; total oxidant status; total anti-oxidant status